KONSEP ANUGERAH ALLAH TERHADAP MANUSIA BERDOSA - Waruwu, Dian Purmawati; Santosa, Yaudi Santos (GENEVA: JURNAL TEOLOGI DAN MISI, 2024)
God gives humans a gift that is completely free. Before receiving God's grace, humanity had lost their glory as a result of sin. The distance between man and God increases as a result of this transgression. However, God chose to act by sending His only begotten Son into the world to atone for and set free the sins of people via Christ's suffering and death so that people could find salvation. Humans receive salvation as a gift from God via the suffering and death of Jesus Christ, not as a result of their own actions. Many individuals misunderstand salvation in this situation and believe that doing nice things will earn them salvation. The author's intention in creating this essay is to help believers understand that receiving salvation is not a result of our good acts, but rather a result of the grace that God has extended to us. However, believers must respond to this favor by believing and having faith in God. The author uses the literary approach to support this piece by gathering library data, precisely recording the findings of observations, and presenting the significant consequences of research into life experiences as a believer in writing. The author also engages with academic articles and additional sources.